Risk of heart failure in elderly patients with atrial fibrillation and diabetes taking different oral anticoagulants: a nationwide cohort study - Shu-Man Lin; Peter Pin-Sung Liu; Yu-Kang Tu; Edward Chia-Cheng Lai; Jih-I Yeh; Jin-Yi Hsu; Kashif M. Munir; Carol Chiung-Hui Peng; Huei-Kai Huang; Ching-Hui Loh (Cardiovascular Diabetology, 2023)
Abstract Background Heart failure (HF) is a critical complication in elderly patients with atrial fibrillation (AF) and diabetes mellitus (DM). Recent preclinical studies suggested that non-vitamin K antagonist oral anticoagulants (NOACs) can potentially suppress the progression of cardiac fibrosis and ischemic cardiomyopathy. Whether different oral anticoagulants influence the risk of HF in older adults with AF and DM is unknown. This study aimed to evaluate the risk of HF in elderly patients with AF and DM who were administered NOACs or warfarin. Methods A nationwide retrospective cohort study was conducted based on claims data from the entire Taiwanese population. Target trial emulation design was applied to strengthen causal inference using observational data. Patients aged  ≥ 65 years with AF and DM on NOAC or warfarin treatment between 2012 and 2019 were included and followed up until 2020. The primary outcome was newly diagnosed HF. Propensity score-based fine stratification weightings were used to balance patient characteristics between NOAC and warfarin groups. Hazard ratios (HRs) were estimated using Cox proportional hazard models. Results The study included a total of 24,835 individuals (19,710 NOAC and 5,125 warfarin users). Patients taking NOACs had a significantly lower risk of HF than those taking warfarin (HR = 0.80, 95% CI 0.74–0.86, p < 0.001). Subgroup analyses for individual NOACs suggested that dabigatran (HR = 0.86, 95% CI 0.80–0.93, p < 0.001), rivaroxaban (HR = 0.80, 95% CI 0.74–0.86, p < 0.001), apixaban (HR = 0.78, 95% CI 0.68–0.90, p < 0.001), and edoxaban (HR = 0.72, 95% CI 0.60–0.86, p < 0.001) were associated with lower risks of HF than warfarin. The findings were consistent regardless of age and sex subgroups and were more prominent in those with high medication possession ratios. Several sensitivity analyses further supported the robustness of our findings. Conclusions This nationwide cohort study demonstrated that elderly patients with AF and DM taking NOACs had a lower risk of incident HF than those taking warfarin. Our findings suggested that NOACs may be the preferred oral anticoagulant treatment when considering the prevention of heart failure in this vulnerable population. Future research is warranted to elucidate causation and investigate the underlying mechanisms.